2022
DOI: 10.1139/cjss-2019-0138
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil pH and nutrient extractability after co-applying biochar and paper mill biosolids

Abstract: Acidification and metal mobility may present challenges in soil receiving paper mill biosolids (PB). Co-applying biochar and PB could help prevent these issues, but its effect must be assessed. The objective of this 224-day incubation study was to evaluate the effect of amending two acidic soils, a clay and sandy‒loam, with two PB types varying in pH (PB1, pH = 7.80; and PB2, pH = 4.51) co-applied with three rates (0%, 2%, and 5% w/w) of pine (Pinus strobus L.) biochar on soil pH and macro (P, K, Ca a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
3
2
0
Order By: Relevance
“…It may be likely because the BA contents also depend upon the type of feedstock, as the wood biochar with high ash contents can have BpH from 4 to 9 . The regression relationship also supported the meta-analysis results and showed that the increase in the BAs significantly decreases the acidic SpH (Table ); this may be because the BAs contained the oxides and hydroxides that contributed to reduce SpH . Moreover, the BC/N ≤ 30 showed a greater effect on increasing the acidic SpH compared to other BC/N subgroups, and these results were also in accordance with the previous literature .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It may be likely because the BA contents also depend upon the type of feedstock, as the wood biochar with high ash contents can have BpH from 4 to 9 . The regression relationship also supported the meta-analysis results and showed that the increase in the BAs significantly decreases the acidic SpH (Table ); this may be because the BAs contained the oxides and hydroxides that contributed to reduce SpH . Moreover, the BC/N ≤ 30 showed a greater effect on increasing the acidic SpH compared to other BC/N subgroups, and these results were also in accordance with the previous literature .…”
Section: Discussionsupporting
confidence: 88%
“…53 The regression relationship also supported the meta-analysis results and showed that the increase in the BAs significantly decreases the acidic SpH (Table 2); this may be because the BAs contained the oxides and hydroxides that contributed to reduce SpH. 54 Moreover, the BC/N ≤ 30 showed a greater effect on increasing the acidic SpH compared to other BC/N subgroups, and these results were also in accordance with the previous literature. 55 The reason may be that when the biochar having a BC/N ≥ 45 is applied to the soil, it takes a longer time to decompose, and during decomposition the organic acids are produced which decrease the soil pH.…”
Section: The Soil Ph Influenced By Biochar Propertiessupporting
confidence: 85%
“…At the end of incubation, soil Mehlich-3 K was from 148 (M550) to 247 mg•kg −1 (M400) higher in biochar-amended soils than in the control, representing an increase of 123%-206% (Table 3). A similar trend was observed in a different 224 d incubation (Manirakiza et al 2020). Authors reported that the Mehlich-3 K concentration increased with the increase of pine biochar application rate in two acidic soils amended with paper mill biosolids, and this effect was primarily due to increasing K input from the biochar itself.…”
Section: Soil K Extractabilitysupporting
confidence: 74%
“…Although biochar amendments can improve soil fertility and N, P, K, and total C content (Biederman and Harpole 2013;Mukherjee et al 2014), this C-rich material is generally not considered as a fertilizer source. The co-application with an organic or inorganic source of fertilizer is often recommended to increase the availability of nutrients in agricultural soil (Abedin 2018;Sánchez-Monedero et al 2019;Abedin and Unc 2020;Manirakiza et al 2020;Omara et al 2020;Ziadi et al 2020). For example, Abedin (2018) added biochar derived from sugar maple (Acer saccharum) at a rate of 20 Mg C ha -1 with half or the full recommended dose of fertilizers and fishmeal.…”
Section: Biochar Effect On Soil Chemical Propertiesmentioning
confidence: 99%